2018
DOI: 10.4155/fmc-2018-0226
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Some β-Carboline Derivatives as Multi-Target Anticancer Agents

Abstract: Aim: Some anticancer β-carbolines exhibited dual inhibition of topo-I and KSP. Methodology/Results: Novel β-carbolines were synthesized and screened for their anticancer activity according to the NCI protocol. Five dose assays results indicated that compounds 9, 10, 12, 17 and 20 were potent and non selective anticancer agents; the sulfanyltriazole 12 was the most potent. Compounds 10, 12 and 20 showed dual topo-I and KSP inhibition with compound 12 being the most potent. Active compounds elicited Pre-G1 apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Consistent with our results, Cao et al indicated that β-carboline alkaloid derivatives and harmine altered the cell cycle distribution by reducing the ratio of cells in the G0/G1 and increasing the ratio in the S and G2/M phases ( 43 ). Further mechanistic studies by Abdelsalam et al showed that β-carboline alkaloid derivatives can trigger sub-G1 upregulation and cause MDA-MB435 cell cycle arrest ( 44 ). In particular, our results showed that DC induced the number of cells in the sub-G1 phase and led to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Cao et al indicated that β-carboline alkaloid derivatives and harmine altered the cell cycle distribution by reducing the ratio of cells in the G0/G1 and increasing the ratio in the S and G2/M phases ( 43 ). Further mechanistic studies by Abdelsalam et al showed that β-carboline alkaloid derivatives can trigger sub-G1 upregulation and cause MDA-MB435 cell cycle arrest ( 44 ). In particular, our results showed that DC induced the number of cells in the sub-G1 phase and led to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…They cause antagonism at 9.4 μM (compound 22 ), 2.50 μM (compound 23) , and 9.30 μM (compound 24 ) against topoisomerase 1. The compounds also antagonize kinase spindle protein (KSP) at 28.58, 8.91, and 19.47 μM, respectively [ 45 ]. Pathway analysis has suggested that the anticancer properties of the compounds are due to G1 apoptosis and cell cycle arrest at the G2/M phase.…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%
“…Variations in the nature of substitution may provide a wide scope of a comparative study of effects on biological activity, polarity, spatial arrangement, chain flexibility, planarity, and conformation of the products. The focus of our research group has been on the development of novel anti-breast cancer agents, and encouraged by previous results, [41,53,54] we desired to explore newer leads and designed and synthesized new series of pyrimidine derivatives. Our strategy aimed at the modification of the prototype, IIIe (Figure 1), [41] and principally consisted of three bioisosteric modifications made by changing the functionalities or positions of the previously established pharmacophores and maintained in almost all synthesized compounds (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…13 C NMR (DMSO-d 6 , 101 MHz) δ: 55 54,. 114.02, 114.24, 122.55, 123.50, 124.88, 127.53, 128.45, 128.97, 129.27, 130.35, 131.05, 132.61, 133.10, 135.30, 141.90, 143.82, 145, 155.58.…”
mentioning
confidence: 99%